Systematic review of facilitated communication 2014–2018 finds no new evidence that messages delivered using facilitated communication are authored by the person with disability. (December 2018) - Hemsley, Bronwyn; Bryant, Lucy; Schlosser, Ralf W; Shane, Howard C; Lang, Russell; Paul, Diane; Banajee, Meher; Ireland, Marie
Background and aims: Facilitated Communication (FC) is a technique that involves a person with a disability pointing to letters, pictures, or objects on a keyboard or on a communication board, typically with physical support from a "facilitator". Proponents claim that FC reveals previously undetected literacy and communication skills in people with communication disability. However, systematic reviews conducted up to 2014 reveal no evidence that the messages generated using FC are authored by the person with a disability. This study aimed to conduct a systematic review of the literature on FC published between 2014 and 2018 to inform the 2018 update of the 1995 American Speech-Language-Hearing Association Position Statement on FC. Method: A systematic search was undertaken to locate articles about FC in English published in the peer reviewed literature since 2014; and to classify these according to the study design for analysis. Studies meeting the inclusion criteria were classified according to four categories of evidence: (a) quantitative experimental data pertaining to authorship, (b) quantitative descriptive data on messages produced using FC, (c) qualitative data, or (d) commentary material on FC. Main contribution: In total, 18 studies met the inclusion criteria. There were no new empirical studies and no new descriptive quantitative studies addressing the authorship of messages delivered using FC. Three new qualitative studies qualified for inclusion; these did not first establish authorship. Of the 15 new commentary papers on FC located, 14 were critical and one was non-critical. The results could be used to inform the development or update of current position statements on FC held locally, nationally, and globally. Conclusion: There are no new studies on authorship and there remains no evidence that FC is a valid form of communication for individuals with severe communication disabilities. There continue to be no studies available demonstrating that individuals with communication disabilities are the authors of the messages generated using FC. Furthermore, there is substantial peer-reviewed literature that is critical of FC and warns against its use. Implications: FC continues to be contested in high profile court cases and its use promoted in school settings and workshops at university campuses in the US. Our empty systematic review will influence both clinical practice and future clinical guidance; most immediately the American Speech-Language-Hearing Association Position Statement on FC and any future guidance issued by the 19 associations worldwide with positions against FC.